Scottish home prices: Compatible with Euro membership? - William Miles (The European Journal of Comparative Economics (EJCE), 2021)
Although the Scottish electorate voted down independence in 2014, Brexit has led to renewed calls from Scottish political leaders for a second referendum. Scottish independence would likely lead to joining the European Union, and this would obligate Scotland to eventually join the euro common currency. If Scottish home prices were not highly cohesive with those in euro zone countries, the ECB's monetary policy could cause major disruptions for Scottish housing, and, by extension, the Scottish economy. As an example, if most euro-country home values were rising, but those in Scotland were falling, the ECB would likely run a tight monetary policy, which would be devastating to housing conditions in Scotland. We accordingly investigate the co-movement of house prices in Scotland with those in eight major euro zone countries, as well as co-movement between Scottish and UK home prices, using a variety of metrics. The use of methods that are primarily linear indicates that joining the euro may not result in a large loss of co-movement with other regional housing markets, compared to Scotland's current correlation with UK national home prices. However, the use of a measure that takes into account differences in the magnitude, and not just the phase of cycles yields results indicating Scotland exhibits very little co-movement with other euro housing markets. Indeed Scotland has co-movement metrics within the euro countries at levels similar to those of Spain and Ireland, which both suffered devastating booms and busts. Thus leaving sterling for the euro could be highly problematic.
Keywords: E32; F45; R31; 330; Housing supply and markets; Business fluctuations; Cycles; Macroeconomic issues of monetary unions